Earth observation technologies in service to the cultural landscape of Cyprus: Risk identification and assessment - Cuca, Branka; Tzouvaras, Marios; Agapiou, Athos; Lysandrou, Vasiliki; Themistocleous, Kyriacos; Nisantzi, Argyro; Hadjimitsis, Diofantos G. (My University, 2016)
The Cultural landscapes are witnesses of "the creative genius, social development and the imaginative and spiritual vitality of humanity. They are part of our collective identity", as it is internationally defined and accepted (ICOMOSUNESCO). The need for their protection, management and inclusion in the territorial policies has already been widely accepted and pursued. There is a great number of risks to which the cultural landscapes are exposed, arising mainly from natural (both due to slow geo-physical phenomena as well as hazards) and anthropogenic causes (e.g. urbanisation pressure, agriculture, landscape fragmentation etc.). This paper explores to what extent Earth Observation (EO) technologies can contribute to identify and evaluate the risks to which Cultural Landscapes of Cyprus are exposed, taking into consideration specific phenomena, such as land movements and soil erosion. The research of the paper is illustrated as part of the activities carried out in the CLIMA project - "Cultural Landscape risk Identification, Management and Assessment". It aims to combine the fields of remote sensing technologies, including Sentinel data, and monitoring of cultural landscape for its improved protection and management. Part of this approach will be based on the use of InSAR techniques in order to monitor the temporal evolution of deformations through the detection and measurement of the effects of surface movements caused by various factors. The case study selected for Cyprus is the Nea Paphos archeological site and historical center of Paphos, which are listed as UNESCO World Heritage sites. The interdisciplinary approach adopted in this research was useful to identify major risks affecting the landscape of Cyprus and to classify the most suitable EO methods to assess and map such risks.
Keywords: Archeology; Climate change; Cultural landscapes; Earth observation; Nea Paphos; Risk assessment; UNESCO